Hubungan Persepsi Perawat tentang Kanker Payudara dengan Perilaku Terhadap Pemeriksaan Payudara Sendiri (SADARI) di Rumah Sakit Siloam Jambi Tahun 2025 - Risna Meliyani; Aguspairi; Aulia Ratnasari Harahap (Universitas Adiwangsa Jambi, 2026)
Background: Breast cancer is a global health concern with high incidence and mortality rates, including in Jambi Province, Indonesia. Early detection through Breast Self-Examination (BSE) is a simple and effective method to improve prognosis. Methods: This quantitative analytical study employed a cross-sectional design, involving 53 female nurses at Siloam Hospital Jambi selected through Simple Random Sampling. Data were collected using structured questionnaires to measure nurses' perceptions of breast cancer and their BSE behavior. Results: The findings indicated that the majority of nurses held negative perceptions towards breast cancer (52.8%) and exhibited poor BSE behavior (50.9%). The Chi-Square test yielded a Pearson Chi-Square value of 28.717 with a p-value of 0.000, demonstrating a statistically significant relationship between nurses' perceptions of breast cancer and their BSE behavior. A Pearson correlation coefficient of 0.736 confirmed a strong positive correlation, implying that more positive perceptions among nurses were associated with better BSE practices. Conclusion: A significant and strong relationship exists between nurses' perceptions of breast cancer and their BSE behavior.